The genus Paragus Latreille (Diptera: Syrphidae) in Iran, with the description of a new species - Gilasian, Ebrahim; Sorokina, Vera S. (Zootaxa, 2011)
A new species of the genus Paragus Latreille is described, Paragus (Paragus) radjabii sp. nov. It is similar to P. compeditus Wiedemann and P. hyalopteri Marcos-García & Rojo. The head, abdomen and male genitalia of the new species are figured. A list of the species of Paragus known from Iran is provided, along with a distributional map of the species in Iran.